2018 IEEE International Conference on Robotics and Automation (ICRA) 2018
DOI: 10.1109/icra.2018.8460203
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Prediction by Planning Using Deep Neural Networks

Abstract: Accurate traffic participant prediction is the prerequisite for collision avoidance of autonomous vehicles. In this work, we predict pedestrians by emulating their own motion planning. From online observations, we infer a mixture density function for possible destinations. We use this result as the goal states of a planning stage that performs motion prediction based on common behavior patterns. The entire system is modeled as one monolithic neural network and trained via inverse reinforcement learning. Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(73 citation statements)
references
References 19 publications
(31 reference statements)
0
72
0
1
Order By: Relevance
“…We subdivided the sequences using a fixed length and a frame rate of 5Hz, i .e. 0.2 second interval between each input, (the original frame rate of the dataset in [38] was 10Hz). In order to augment the data we used a sliding window of 1 time step (varying 0.1 seconds).…”
Section: Methodsmentioning
confidence: 99%
“…We subdivided the sequences using a fixed length and a frame rate of 5Hz, i .e. 0.2 second interval between each input, (the original frame rate of the dataset in [38] was 10Hz). In order to augment the data we used a sliding window of 1 time step (varying 0.1 seconds).…”
Section: Methodsmentioning
confidence: 99%
“…However, Pendleton et al () do not include a review on deep learning technologies, although the state‐of‐the‐art literature has revealed an increased interest in using deep learning technologies for path planning and behavior arbitration. Following, we discuss two of the most representative deep learning paradigms for path planning, namely IL (Grigorescu, Trasnea, Marina, Vasilcoi, & Cocias, ; Rehder, Quehl, & Stiller, ; Sun, Peng, Zhan, & Tomizuka, ) and DRL‐based planning (Paxton, Raman, Hager, & Kobilarov, ; L. Yu, Shao, Wei, & Zhou, ).…”
Section: Deep Learning For Path Planning and Behavior Arbitrationmentioning
confidence: 99%
“…The goal in IL (Grigorescu et al, ; Rehder et al, ; Sun et al, ) is to learn the behavior of a human driver from recorded driving experiences (Schwarting, Alonso‐Mora, & Rus, ). The strategy implies a vehicle teaching process from human demonstration.…”
Section: Deep Learning For Path Planning and Behavior Arbitrationmentioning
confidence: 99%
“…IRL is conditioned on the goal destination of the VRU, but it is possible to estimate the goal online jointly with the future path. For instance, Rehder et al [8] estimate the goal using a neural net that combines image data with the previous path of the VRU. Ballan et al [9] learn preferred routes directly on image data rather than the semantic information, and show that the learned knowledge is transferable to new locations.…”
Section: Previous Workmentioning
confidence: 99%